Spatial Finance : Challenges and Opportunities in a Changing World - World Bank; WWF (World Bank, Washington, DC, 2020)
If financial markets are to realign towards truly sustainable development the financial sector needs to differentiate commercial actors more accurately on their climate and environmental performance. A potential breakthrough to help in this challenge is the emerging field of ‘Spatial Finance’, the independent assessment of the location of a company’s or a country’s assets and infrastructure using ground data, remote sensing observations and modelled insights, offers a potentially transformative means to gain improved quantitative ESG insights. Rapid development is required if spatial finance is to deliver in the short term. In this report, authors outline a possible taxonomy and hierarchy for spatial finance, showing how discrete forms of technology, approaches and data can be considered within a single consistent framework. Using this framework, spatial finance could provide insights at differing scales for different applications from the asset-scale for project finance, to company-scale for investment, to country scale for sovereign debt. Throughout the document authors provide insights into current cutting-edge developments within the field, illustrated with case studies from practitioners and data providers, and explore potential future developments.